A STUDY ON EMPLOYEES SATISFACTION WITH REFERENCE TO TEXTILE SHOP (International Journal of Food and Nutritional Sciences, 2022)
The employee satisfaction activities have been formulated on conviction that it is man behind the machine who is responsible for achieving mission of an organization. A person can deliver at his best only when he is satisfied and committed to the cause. To keep the employees motivated and committed various satisfaction facilities are provided by the organization not to the employees but also to their family members too, in this study deeply consider all factors pertaining to employees satisfaction.